The Intra-aortic Balloon Pump (IABP)- An Essential Component of Modern Cardiac Care - Safiuddin, Dr Mohammad (University Heart Journal, 2012)
Not available DOI: http://dx.doi.org/10.3329/uhj.v8i1.11658 University Heart Journal Vol. 8, No. 1, January 2012